Conservation tourism as a strategy to promote the conservation of biodiversity among BRICS countries - Carvalho-Junior, Oldemar de Oliveira; Desai, Minal (Revista Brasileira de Ecoturismo (RBEcotur), 2021)
This work aims to discuss tourism among BRICS members, especially between Brazil and India, considering the pandemic caused by COVID-19 and how tourism can help overcome this crisis, promoting biodiversity conservation among member countries. Historical and current data from official international sources, in Brazil and India's government, were obtained and analyzed to create an overview of the current status of tourism among BRICS countries. India represents only 15% of the total tourists who come to Brazil. In Santa Catarina, an important tourist destination in southern Brazil, in 2018, only 56 tourists came from Russia, 39 from China, 32 from India, and 25 from South Africa. As a consequence of COVID-19, tourism will likely have to reinvent itself or, at least, be aware of other windows of opportunity for its survival and growth. As a result, experiential tourism, such as conservation tourism, is expected to consolidate more strongly. Conservation tourism, an innovative proposal, can be defined as the tourism segment that uses natural and cultural heritage, through a socio-environmental research project, with the participation of ecovolunteers, promoting the social entrepreneurship of the communities involved, focused on the experience and learning in protected areas, contributing to their planning, use, sustainability, and conservation, with social responsibility. The difference between conservation tourism and ecotourism is that conservation tourism generates information, unlike ecotourism, which uses available information. This type of tourism, conservation, and community base, with research and education bias, can represent an essential agenda of approximation between the BRICS countries. The definition of a cooperation agenda can be fundamental to promote conservation tourism while helping to protect biodiversity, generating jobs, and being a source of income for the communities involved.